1998
DOI: 10.1097/00007890-199804270-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Immunosuppressive Agents on Acute Pancreatitis

Abstract: The present results suggest that AZA and high doses of CsA aggravate acute pancreatitis and should, therefore, be avoided once posttransplantation pancreatitis has been suspected, whereas lower doses of CsA, OKT3, and PRED may be used safely. PRED can even be used at higher doses as may be required when graft rejection is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…There is also a number of case reports where acute pancreatitis was associated with Crohn's disease alone and several studies have reported pancreatic insufficiency in Crohn's disease [23][24][25][26][27] In addition, one study showed that in an animal model of acute pancreatitis in rats, the use of azathioprine worsened the inflammation. 28 These findings taken together might suggest that azathioprine exacerbates an already inflamed pancreas in Crohn's disease.…”
Section: Discussionmentioning
confidence: 97%
“…There is also a number of case reports where acute pancreatitis was associated with Crohn's disease alone and several studies have reported pancreatic insufficiency in Crohn's disease [23][24][25][26][27] In addition, one study showed that in an animal model of acute pancreatitis in rats, the use of azathioprine worsened the inflammation. 28 These findings taken together might suggest that azathioprine exacerbates an already inflamed pancreas in Crohn's disease.…”
Section: Discussionmentioning
confidence: 97%
“…Empirical reduction of dosage or withdrawal of azathioprine is one of the strategies recommended. Experimental evidence suggests that prednisolone, low doses of cyclosporine, and OKT3 monoclonal antibodies are well tolerated in murine pancreatitis but azathioprine and high doses of cyclosporine may aggravate pancreatic injury (9). All of our five patients had evidence of recent viral infection – chicken pox in two, CMV in two and hepatitis E in one.…”
Section: Discussionmentioning
confidence: 99%
“…After the operation, there was a late onset of graft function and the patient was haemodialysis dependent. A biopsy performed 7 days after transplantation confirmed severe combined acute cellular (2B according to Banff 2007 classification) and antibody mediated C4d positive rejection, which was treated intravenously with rabbit antithymocyte globulin (700 mg in 7 doses á 100 mg) in parallel with plasmapheresis [7] and intravenous immunoglobulins (total dose 75 mg). This treatment was successful, with recovery the graft function.…”
Section: Presentation Of Casementioning
confidence: 99%